A Conceptual Visibility Framework for Linking Spatial Metrics With Experience and Organizational Outcomes. (October 2020) - Lim, Lisa; Zimring, Craig M.
Visibility enables or prohibits healthcare professionals' ability to monitor, control, or manage situations in healthcare settings. Visibility has a significant impact on patient safety, including patient fall rates and mortality rates, and on the performance of healthcare professionals, including situational awareness and communication. This article provides a conceptual visibility framework synthesizing visibility analysis models, tools, and metrics. The framework uses four dimensions that capture the experiential phenomena of users, such as visual relationships between specific sets of users/targets, how the orientation of the seeing entity changes visibility patterns, and the unequal visibility levels of seeing and being seen. The framework particularly focuses on how the layout and the resulting patterns of visibility reflect and influence the user experience and organizational functions. By illustrating the similarities and differences of various models in the framework according to the dimensions, this article describes how various visibility analysis models, tools, and metrics can be applied to design and research.